Improving Students’ Motivation in Learning English through Gamification - Amalia, Tasya; Inayati , Dian; Marini, Arita (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
In the event of world pandemic of COVID-19, emergency remote learning settings have become normalized in Indonesia and it has affected students’ motivation in learning. Educators around the world have found a way to enhance students’ motivation through gamification. Therefore this study aims to improve students’ motivation in learning English  through gamification in online learning settings. This study was conducted at a Private Junior High School with 36 eighth graders. The method used in this study is Classroom Action Research (CAR). After conducting two cycles in the implementation phase, the result, supported by the questionnaire, interview, and observation data, shows how gamification is able to improve students’ motivation. In collecting the data, qualitative and quantitative method were used. The questionnaire as the quantitative data, consist of subdimensions of intrinsic and extrinsic motivation. As for the qualitative method, to identify the students’ problem, observation and an end-of-cycle interview were conducted. Through two cycles, the implemented action was able to improve students’ motivation in English class and enlighten the ambience of the class. Although students’ response to gamification was highly favorable, the findings also suggest a new issue. Some students have developed a speech anxiety by learning online due to fear of making mistakes and a feeling of embarrassment. The current study has been able to shed lights on the benefits of gamification in a teaching and learning process of English Language Teaching (ELT).